PENGARUH KEMAMPUAN BERPIKIR KRITIS SISWA DENGAN PROJECT BASED LEARNING MATERI SUHU KALOR - Sumardiana Sumardiana (JURNAL ILMIAH GLOBAL EDUCATION, 2020)
Critical thinking skills can be grown with learning project based learning models. The purpose of this study was to analyze Critical Thinking abilities with project-based learning (PjBL) students at temperature and heat at the high school level. This research was conducted at SMAN 2 BATU,class XI. The subjects of this study were 35 students. This type of research is a mixed method embedded in experimental models. With a test of critical thinking skills the essay forms as many as 8 items. The results showed that there were differences in critical thinking of students before and later getting PjBL training on the material heat and temperature. The result of the research showed that students’ critical thinking has  increas. students' critical thinking skills in temperature and heat material through Project Based Learning learning experienced a significant increase with an average N-Gain score of 0.6 (medium category);  students' critical thinking skills generally experience positive changes both at the reasoning, argument analysis, decision hypothesis, possibility analysis and uncertainty stages.